Effective and Sustainable Reintegration of the Children of Boko Haram Returnees from an Islamic Perspective; a Case Study of Maiduguri Town - Ibrahim Abubakar Mustapha; Muhammad A Ajiri; Ibrahim Lawan Mustapha; Yagana Goma; Abba Kale (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose – This study examines the effective and sustainable reintegration of children of Boko Haram returnees from an Islamic perspective in Northeast Nigeria. The research addresses the persistent social stigma, fear, discrimination, and mistrust faced by these children in post-conflict communities. It argues that reintegration should not only focus on security and humanitarian dimensions but also incorporate Islamic ethical values to foster reconciliation, peace-building, and long-term community healing. Design/methods/approach – The study employed a qualitative research design using Focus Group Discussions (FGDs) with community members and Key Informant Interviews (KIIs) involving Islamic scholars (Ulama), traditional rulers, camp managers, and humanitarian actors. In addition, document analysis was conducted on Qur’anic verses, Hadith, and Islamic literature concerning forgiveness, justice, rehabilitation, and child protection. The collected data were analyzed thematically to identify major barriers to reintegration and the role of Islamic teachings in promoting social cohesion. Findings – The study found that children of Boko Haram returnees are largely perceived as victims of conflict rather than perpetrators of violence. However, stigma, social isolation, fear, and discrimination remain major obstacles to successful reintegration. Sustainable reintegration requires community sensitization, psychosocial support, access to education and vocational empowerment, and the active involvement of religious and traditional institutions. Islamic values such as rahmah (compassion), tawbah (repentance), ‘adl (justice), and collective responsibility significantly contribute to social healing and reconciliation. Research implications/limitations – The study is limited to selected communities in Northeast Nigeria and relies mainly on qualitative data, which may limit broader generalization. Nevertheless, the findings provide important insights for policymakers, humanitarian agencies, and religious leaders in designing culturally and religiously sensitive reintegration programs. Originality/value – This study offers a faith-based reintegration framework that integrates Islamic teachings with modern reintegration theories. It highlights the underutilized role of mosques, Sangaya and Islamiya schools, zakat institutions, and Ulama in supporting sustainable reintegration and preventing future radicalization.